I'm using sage 7.1 and this code here returns `false`

.

```
M = matrix ([[sqrt(1-1/2),1/2],[1,-sqrt(1-1/2)]])
N = matrix ([[sqrt(1-1/3),1],[1/3,-sqrt(1-1/3)]])
(M*N).inverse() == N.inverse()*M.inverse()
```

What is going on?

1 | initial version |

I'm using sage 7.1 and this code here returns `false`

.

```
M = matrix ([[sqrt(1-1/2),1/2],[1,-sqrt(1-1/2)]])
N = matrix ([[sqrt(1-1/3),1],[1/3,-sqrt(1-1/3)]])
(M*N).inverse() == N.inverse()*M.inverse()
```

What is going on?

Copyright Sage, 2010. Some rights reserved under creative commons license. Content on this site is licensed under a Creative Commons Attribution Share Alike 3.0 license.